Converse Theorems for the Cesàro Summability of Improper Integrals - Sefa Anıl Sezer; Rahmet Savaş (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thispaper we prove converse theorems to obtain usual convergence of improperintegrals from Cesàro summability.